Environmental responsibility in Chile. Analysis based on community and Spanish regulations - Pinochet Abalos, María Jesús (M+A. Revista Electrónica de Medioambiente, 2017)
The law Nº 19.300 of 1994, base on the Environment, among other things, integrated into the legal system rules that has been constituted a special regime of environmental responsibility. Then, with the reforms introduced by the Law Nº 20.417 of 2010 and the Law Nº 20.600 of 2012, which have created the new environmental institutionality, the Environmental Courts is recognized as a competent part to know the actions of reparation for environmental damage. In this context, it is necessary to carry out a review of the environmental liability regulation in order to clarify the modifications that have contributed to the improvement of the system. The study is based on 2004/35/ EC Directive on environmental liability in relation to the prevention and repair of environmental damages, with the Law Nº 26/2007 on Environmental Responsibility.
Keywords: Environmental responsibility; environmental damage; environmental damage repair.